Brand Equity Eiger: Studi Mix Method Dalam Industri Outdoor Tangerang - Aurelien, Rafelia; Yerinda, Dini; Yasinta, Kharisma Dewi; Purwadi, Asep Rana; Abdullah, Muhammad (Masyrif : Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
This study analyzes Eiger's brand equity in the outdoor industry in Tangerang using a mixed-method approach, combining quantitative surveys and qualitative interviews. Brand equity is evaluated through four dimensions: brand awareness, brand association, perceived quality, and brand loyalty. Respondents were selected using purposive sampling to ensure direct experience with the brand. The results indicate that Eiger has strong brand equity. Brand awareness is notably high, with the brand recognized as a symbol of quality and reliability. Positive brand associations are linked to innovation and product durability, while perceived quality significantly contributes to consumer loyalty. Many respondents expressed satisfaction and commitment to the brand. This study recommends increasing brand visibility and reinforcing positive associations related to quality and innovation. The findings offer strategic insights and a foundation for further research on brand equity dynamics in local markets and the outdoor industry.